Worries About COVID-19 and Adolescents' Mental Health and Life Satisfaction: The Role of Sociodemographics and Social Support - Rodríguez-Cano, Rubén; Cortés-García, Laura; Ulset, Vidar S.; von Soest, Tilmann (Frontiers in Pediatrics, 2022)
Worries related to the COVID-19 pandemic are associated with mental health problems and reduced life satisfaction. However, the association between different types of worries about COVID-19 and adolescent mental health is unclear. Moreover, there is a lack of information about whether certain groups of adolescents are more vulnerable to the adverse effects of worries and how social support may moderate these effects. Adolescents (N=12,686) completed a survey during the lockdown in spring 2020 in Oslo, Norway (37% response rate, 56.4% girls). The results showed that adolescent worries could be categorized into worries related to infection and those related to the general negative effects of the pandemic. Multivariate regression analyses showed that both types of worries were negatively related to positive affect and life satisfaction and positively related to depressive symptoms. Interaction analyses indicated that some associations with positive affect and depressive symptoms were stronger among adolescents with non-migrant backgrounds, higher family SES, and high reported levels of social support and physical contact during the pandemic. The findings suggest that COVID-19 worries may have negative effects on mental health and inform strategies to increase tailored psychological interventions to mitigate the effect of worry on adolescents’ mental health and life satisfaction.